The Role of Brachytherapy Alone and in Combined Treatment of Esophageal Cancer—A Review - Paweł Cisek; Aleksander Strąk; Paulina Stachyra-Strawa; Andrzej Majdan; Ludmiła Grzybowska-Szatkowska (Applied Sciences, 2024)
Every year, over 600,000 new cases of esophageal cancer are registered worldwide. Treatment depends on the stage of the disease. In the early stages, surgical treatment is the basis (T1–T2 lesion < 3 cm, N0M0), while in more advanced stages, surgical treatment is preceded by radiochemotherapy or only radiochemotherapy is used. In the case of generalized disease, the main treatments used are systemic treatments of chemotherapy, immunotherapy and palliative teleradiotherapy or brachytherapy. Brachytherapy can be used at virtually any stage of disease, both as a radical treatment and as a palliative treatment. This paper presents the possibilities of using brachytherapy at various stages of esophageal cancer treatment. Particular attention was paid to the role of combining brachytherapy and immunotherapy and the possibility of an abscopal effect.